Compensating the losers of free trade - Zareh Asatryan; Sebastian Braun; Wolfgang Lechthaler; Mariya Mileva; Catia Montagna (WWWforEurope, 2014)
Fears of rising wage inequality and job loss loom large in current debates on free trade. Surprisingly, however, there exists little academic research on how to compensate those who lose from free trade. This policy paper reviews the existing theoretical literature on trade and compensation, and derives guidelines on how to design compensation schemes in practice. The existing theoretical literature suggests that active labour market policies, targeted to workers who lose from free trade, are a promising way of compensation. In line with this theoretical recommendation, we find that countries open to free trade also spend more on active labour market policies.
Keywords: F10; F20; J30; J60; 330; Challenges for welfare system; Globalisation; Labour markets; Policy options; Welfare state